Optimal Location of New Forests in a Suburban Area - Ellen Moons; Bert Saveyn; Stef Proost; Martin Hermy (European Regional Science Association (ERSA), 2005)
In this paper we develop a methodology to select a combination of forest sites that maximizes net social benefits taking into account restrictions on the total surface/size of new forest land. We use GIS technology to estimate for each site the major cost and benefit elements including lost agricultural output, timber and hunting values, carbon sequestration, non-use and recreation benefits. Special emphasis is placed on the recreational value of a potential site as this raises two issues. First, the recreation benefits of a base site estimated via the travel cost method need to be transferred to all potential sites. Second, the recreation benefit of each potential site depends on the existing sites and on the other sites that are in the selection. We show that the same 'amount' of afforestation (i.e. the same total surface divided into multiple sites at varying locations) creates a wide range of potential net social benefits due to the role of a varying set of recreation substitutes.We show that the net social benefit of new forest combinations respecting the area constraints may differ up to a factor 21. The substitution effect between forests, both new and existing, turned out to be the dominant factor in the benefit estimation. Compared to the existing literature, our paper improves the methodology by working with realistically feasible sites rather than grid sites, by including the complex recreation substitution effects between potential sites and by including all costs and benefits of afforestation bringing the analysis closer to a real cost benefit analysis.
Keywords: 330